PENERAPAN PENDEKATAN KONSTRUKTIVISME SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN INTERPRETATIF BAGI SISWA - Fimeir Liadi; Abu Darim; Tri Warjuningsing (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2018)
Reading is an important language skill for students. Through reading, students are able to get lots of information from various reading sources. However, after observation and interview are conducted, it shows that the ability of interpretative reading comprehension for the students still needs to be improved. Therefore, the researcher thinks that the improvement of the students’ ability in interpretative reading comprehension can be done by using constructivism approach.In relation with the effort to improve the ability in interpretative reading comprehension, the specific problem limitation studied is as follow. How far is the implementation of constructivism approach in pre reading stage, while reading stage, and post reading stage can improve the ability of interpretative reading comprehension for the students of the grade? In accordance with it, the specific objective of this research is to describe the implementation of constructivism approach in pre reading stage, while reading stage, and post reading stage.Keywords: Constructivism approach, interpretative reading comprehension